Nitric Oxide-Releasing Chitosan for the Treatment of Multi-Drug Resistant Superbugs. (4th October 2017) - Kougoulos, Terry; Schoenfisch, Mark; Cruz, Pedro De Jesus; Ahonen, Mona; Fisher, Nathan
Abstract: Background: Multi-drug resistant superbugs are a serious health threat due to limited treatment options and high mortality rates. Certain superbug strains are now resistant to as many as 36 representative FDA-approved antibiotics, including Colistin and Carbapenem antibiotics, widely considered as the last line of defense against untreatable infections. Nitric oxide (NO) is a diatomic free radical employed by the immune system to eradicate bacteria via oxidative and nitrosative stress. To facilitate storage and controlled release of NO, we have developed NO donor-modified biopolymers based on chitosan, a linear polysaccharide composed of randomly distributed β--linked D-glucosamine and N-acetyl-D-glucosamine. Herein, we report the broad spectrum antibacterial action of low molecular weight (5 kDa) NO-releasing chitosan against Gram-positive and Gram-negative multi-drug-resistant bacterial species, including Klebsiella pneumoniae, Staphylococcus aureus, and Pseudomonas aeruginosa . Methods: MIC assays were performed using CLSI guidelines in a 96-well plate format. All assays were carried out in triplicate using a two-fold dilution range. The bacterial suspension was then diluted in assay medium to a target concentration of approximately 5 × 10 5 CFU/mL, after which it was added to all test and growth control wells, and allowed to incubate. Test wells were scored for the lowest NO concentration released from the chitosan to inhibit visual growth of the pathogen. After MIC determination, wells demonstrating inhibition were plated, incubated and resulting colonies counted to determine survival concentration. The lowest concentration of NO to inhibit ≥99.9 % of a given test organism was reported as the MBC. Of note, chitosan alone showed no antibacterial action. Results: MIC and MBC assays for NO-releasing chitosan against six multi-drug resistant strains are provided below. Conclusion: The properties of the NO-releasing chitosan, including water solubility, make it an excellent drug candidate for treating respiratory infections. Such development is currently underway. Disclosures: All authors: No reported disclosures.